Mechanism and Implementation of Murabahah Agreement on Motorcycle Financing for ASN Bank Sumut Syariah KCPS Hm Yamin - Muhammad Alwi Setiawan; Ria Armayani Hasibuan (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
This study was made to explain the mechanism and implementation of the murabahah contract in motorcycle financing for the state civil apparatus (ASN) which is run by a syriah Sumatran bank. In the implementation process, Bank Sumut Syariah will provide terms and conditions that must be met by customers who wish to apply for motorcycle financing for this ASN. The customer must also follow the procedures set by Bank Sumut Syriah. Motorcycle financing procedures for ASN at Bank Sumut Syariah KCPS HM Yamin. In this motor vehicle financing, the Bank of North Sumatra Syariah acts as a financing institution, not as a pure seller who provides goods needed by customers. Bank Sumut Syariah will only buy products in accordance with the terms of the murabahah contract made to financing customers. Bank Sumut Syriah has complied with the provisions and farwa of the Sharia Supervisory Board NO.04/DSN-MUI/IV/2000 regarding murabahah financing in implementing murabah financing.